2020
DOI: 10.4236/ae.2020.81004
|View full text |Cite
|
Sign up to set email alerts
|

Co-Existence of <i>Bactrocera dorsalis</i> Hendel (Diptera: Tephritidae) and <i>Ceratitis cosyra</i> Walker (Diptera: Tephritidae) in the Mango Orchards in Western Burkina Faso

Abstract: Fruit flies (Diptera: Tephritidae) are one of the insect groups that menace the horticultural sector in sub Saharan Africa. The main fruit fly species that caused mango fruits (Mangifera indica L.) damage in Western Burkina Faso include Bactrocera dorsalis Hendel and Ceratitis cosyra Walker. This work was carried out in Western Burkina Faso to study the relationships between these two insect pests on mango fruits in mango orchards. Thirty mango fruits per variety were sampled in six mango orchards every two we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Our results showed that B. dorsalis did not displace the indigenous species C. cosyra and C. silvestrii from mango and shea fruits, respectively, in Western Burkina Faso, but had led to a decrease of their infestation rates. This had also been concluded by Zida et al (2020). The results of this study therefore corroborate previous studies showing that, where exotic tephritid species have been introduced into areas already occupied by a native tephritid species, interspecific competition occurs and result in a decrease in numbers and niche shifts of the indigenous species, albeit without leading to complete exclusion (Duyck et al, 2004;Ekesi et al, 2009;Mwatawala et al, 2009).…”
Section: Interspecific Competition Between Fruit Fly Speciessupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that B. dorsalis did not displace the indigenous species C. cosyra and C. silvestrii from mango and shea fruits, respectively, in Western Burkina Faso, but had led to a decrease of their infestation rates. This had also been concluded by Zida et al (2020). The results of this study therefore corroborate previous studies showing that, where exotic tephritid species have been introduced into areas already occupied by a native tephritid species, interspecific competition occurs and result in a decrease in numbers and niche shifts of the indigenous species, albeit without leading to complete exclusion (Duyck et al, 2004;Ekesi et al, 2009;Mwatawala et al, 2009).…”
Section: Interspecific Competition Between Fruit Fly Speciessupporting
confidence: 91%
“…This had also been concluded by Zida et al . (2020). The results of this study therefore corroborate previous studies showing that, where exotic tephritid species have been introduced into areas already occupied by a native tephritid species, interspecific competition occurs and result in a decrease in numbers and niche shifts of the indigenous species, albeit without leading to complete exclusion (Duyck et al ., 2004; Ekesi et al ., 2009; Mwatawala et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the native mango/marula fly C. cosyra is steadily being displaced by the invasive B. dorsalis (Ekesi et al ., 2009). Nevertheless, recent studies in Burkina Faso have reported a relatively stable co-existence between C. cosyra and B. dorsalis (Zida et al ., 2020). The co-infestation of both species at the colour break phenological stage observed during this study confirms this stable co-existence among these two species depending on favourable environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…long, are performed at 37-42°C and offer high sensitivity even with minuscule amounts of starting material (Aman et al 2020). Amplification of a pool of several specimens is of great benefit since co-infestation of fruit by different Tephritidae and Drosophilidae families occur regularly (Deus et al 2016;Zida et al 2020;Moquet et al 2021). Therefore, an amplification method that allows the pooling of different specimens as well as multiplexed detection of the different targets in the pool can prove beneficial for simple in-situ detection of pests.…”
Section: Introductionmentioning
confidence: 99%
“…23 Amplification of a pool of several specimens is of great benefit since co-infestation of fruit by different Tephritidae and Drosophilidae families occurs regularly. [24][25][26] Therefore, an amplification method that allows the pooling of different specimens as well as multiplexed detection of the different targets in the pool can prove beneficial for simple in situ detection of pests.…”
Section: Introductionmentioning
confidence: 99%